Comparison of BCG Tokyo172 Strain Induction Therapy Between Low Dose and Standard Dose for Non-Muscle Invasive Bladder Cancer: Intravesical Instillation of BCG Tokyo172 Strain - Hideyuki Isobe; Fumitaka Shimizu; Takeshi Ieda; So Nakamura; Naoko Takazawa; Hanna Suetsugu; Kazunori Kajino; Shu Hirai; Hisashi Hirano; Katsuhito Yuzawa; Shigeo Horie (Biomedicines)
Objectives: The aim of this study was to identify factors that predict recurrence by comparing low-dose and standard-dose Bacillus Calmette-Guérin (BCG) induction therapy in patients with non-muscle invasive bladder cancer (NMIBC). Methods: A total of 273 consecutive NMIBC patients who received low-dose (40 mg) or standard-dose (80 mg) BCG intravesical instillation therapy between January 2004 and December 2023 were analyzed. Recurrence-free survival (RFS) rates were assessed using the Kaplan–Meier method with the log-rank test. Univariate and multivariate Cox proportional hazards regression analyses were used to identify independent predictors of recurrence based on the Club Urológico Español de Tratamiento Oncológico (CUETO) criteria. Results: The log-rank test showed that older age, low BCG dose, number of tumors, and a history of recurrence increased the risk of recurrence significantly. Regarding older patients, recurrence rates were similar between the two dose groups. However, younger patients had significantly lower recurrence rates with standard-dose BCG compared to low-dose BCG. Multiple Cox regression analysis confirmed that older age, low-dose BCG, greater than three tumors, and a history of recurrence were significant predictors of recurrence. Conclusions: In this study, we found that low-dose BCG induction therapy was associated with higher relapse rates compared with standard doses, especially in younger patients. Age-related differences in the immune response to BCG may influence these relapse patterns.